Minecraft : the island - Brooks, Max.; Mojang AB (Firm) (New York : Del Rey, 2017)
"An official tie-in to the globally popular video game traces the story of a new hero stranded in the world of Minecraft who must survive a harsh environment while unraveling the secrets of a mysterious island."--OCLC.
6.3
3-6
3-6
790L
Keywords: Minecraft (Game) -- Juvenile fiction; Video games -- Juvenile fiction; Minecraft (Game) -- Fiction; Video games -- Fiction; Adventure and adventurers -- Fiction; Minecraft (Game) -- Fiction; Video games -- Fiction; Action and adventure fiction